2008
DOI: 10.1007/s12032-008-9050-6
|View full text |Cite
|
Sign up to set email alerts
|

Study of distinct protein profiles for early diagnosis of NSCLC using LCM and SELDI-TOF-MS

Abstract: No biomarker has been available to detect early lung cancer so far. The aim of this study is to screen biomarker patterns for early diagnosis of non-small cell lung cancer (NSCLC) using laser capture microdissection (LCM) and surface-enhanced laser desorption ionization time-of-flight mass spectrometry (SELDI-TOF-MS). The 3 groups of the interested cells from 13 NSCLC tissues, 11 normal lung tissues (out of the 13 NSCLC patients), and 6 benign lung diseased tissues (BLD) were successfully separated by LCM, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Recently, SELDI-ToF-MS profiling has been applied in a few studies aimed to identify lung cancer biomarkers analyzing tissue [19-22] and serum samples [23-28]. Unfortunately, although the obtained results are quite promising, so far none of the discovered biomarker has already been validated for the clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, SELDI-ToF-MS profiling has been applied in a few studies aimed to identify lung cancer biomarkers analyzing tissue [19-22] and serum samples [23-28]. Unfortunately, although the obtained results are quite promising, so far none of the discovered biomarker has already been validated for the clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…The cut off value depended on different statistic algorithm. Liao (26) study involved in statistic algorithm was SPSS 13.0, and studies of Yang (20) and Yang (17) were support vector machine (SVM). Remains were decision tree classification.…”
Section: Resultsmentioning
confidence: 99%
“…It is noted that SELDI-TOF-MS can also contribute to the ongoing human proteome studies, as proposed for the total proteins in the serum and other samples. SELDI-TOF-MS based protein profiling has been successfully applied in identification of different cancers and cancer-related biomarkers in diverse diagnostic samples as serum, plasma and tissue biopsies (20). When combined with radiological data, SELDI may bring patients new hopes in the early detection of NSCLC inside even before the onset of symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, >50% of patients diagnosed with NSCLC are at stage IIIB or IV disease, which is not only difficult to treat, but also increases pathologic material guiding systemic therapy (37). Therefore, a number of reports suggest that early diagnosis is beneficial for the treatment of NSCLC and may contribute to survival rate for patients in clinic (25,38). Previous research has indicated that contrast-enhanced ultrasound has been widely applied in NSCLC diagnosis (39).…”
Section: Discussionmentioning
confidence: 99%